Laparoscopic Heller myotomy with Dor fundoplication for achalasia: an outcome in a tertiary health center of Nepal - Deo, Kunal Bikram; Regmi, Parbatraj; Pandit, Narendra; Yogi, Barurendra Raj; Sah, Bed Prakash; Budhathoki, Ulav; Adhikary, Shailesh (Frontiers in Surgery, 2026)
IntroductionLaparoscopic Heller Myotomy with Dor fundoplication is the most effective therapeutic option for Achalasia cardia, with fewer complications. We present the outcomes of this procedure with long-term follow-up in patients with Achalasia cardia.MethodsA single institution prospectively maintained data of Laparoscopic Heller Myotomy with Dor fundoplication between January 2014 and January 2024 was reviewed. Eckardt scores at three-time points (preoperative, 3-month, and long-term follow-up) were used to assess treatment efficacy.ResultsA total of 16 patients had a median age of 34 years. Megaesophagus was observed in 8 (50%) patients, and 5 patients had sigmoid esophagus. The mean operative time was 162 ± 41 min. The mean myotomy length was 6.1 cm and 2.19 cm, respectively, for the esophagus and the stomach. Following the surgery, there was significant improvement in the Eckardt score from a median preoperative score of 9 (5–12) to a median postoperative score of 2(0–4) in 3 months (p = 0.001) and a median Eckardt score of 1.5 (0–3) in long-term follow-up (P < 0.001). The median long-term follow-up was 32 months (12–60 months). Overall, two treatment failure was observed, and one required endoscopic balloon dilatation. The gastroesophageal reflux (uncomplicated) was observed in 5 (31.2%) patients. The symptoms were mild, and none had reflux-related complications at the last follow-up.ConclusionsLHM provides immediate and durable symptomatic relief with fewer complications.